Media Oxygen Consumption Level for A Seed Brek Fish (Puntius Orphoides) - Asep Rachmat Pratama; Elinah Elinah; Iskandariah Iskandariah (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2022)
Disolved oxygen plays an important role for fish living in its life environment. Information on the ammount of oxygen consumption of a fish in certain volume of water is needed in order to give balancing between the ammount of disolved oxygen and fish in it. The objective of this research is obtaining oxygen consumption level of a juvenile of brek fish (Puntius orphoides) of 5-7 cm body length. Oxygen consumption of fish was measured using a tube that equiped with DO tool (dissolved oxygent, DO), and the tube was filled by fresh water. Measurement of oxygen consumption of juvenil was done by measuring the concentration of dissolved oxygen from fresh water in the respirometer tube, began when fish had entered into the respirometer tube up to two hours observation. The result showed that oxygen consumption rate a juvenile of brek fish (Puntius orphoides) of 5-7 cm length, is ranging between 0.816 and 1.734 mg/hour.